Squamous Cell Carcinoma with Co-infection of Microsphaeropsis arundinis and Geotrichum candidum: A Rare Case Report - Afany, Nurul Athirahwanti; Djawad, Khairuddin (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Squamous cell carcinoma (SCC) is a non-melanoma skin cancer is a malignant carcinoma with an increasing incidence. The diagnosis of SCC is mainly based on clinical features and an excisional biopsy with histologic confirmation should be performed on all clinically suspected lesions to determine the prognostic and management of SCC. The first-line treatment of SCC of the skin is complete surgical excision. Microsphaeropsis arundinis and Geotrichum candidum are types of fungi that can infect the skin. CASE REPORT: We report a case of a 46-year-old female patient that was diagnosed with SCC based on clinical, dermoscopy, and histopathological features. In addition, M. arundinis and G. candidum were also found on culture examination, where these fungi are rarely found, especially in cases of SCC. CONCLUSION: The patient underwent tumor excision and amputation.